SOCIO-POLITICAL TRANSFORMATION OF MYANMAR SOCIETY (EVOLUTIONARY ANALYSIS OF THE BRITISH COLONIAL ERA) - Hasti Sulaiman; Mohamad Zaitun (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to examine the socio-political transformation of Myanmar society during the British colonial era by employing an evolutionary analysis approach. British colonial rule, spanning from the 19th century to the mid-20th century, not only altered Myanmar's traditional system of governance but also brought about significant changes to the society's social, economic, cultural, and political structures. The study seeks to analyze the transformation of Myanmar society from a kingdom-based system rooted in monarchical power and traditional hierarchies toward a more bureaucratic and integrated colonial administrative structure. The research methodology employed is a literature review utilizing a historical-critical approach, involving the analysis of various scholarly sources regarding Myanmar's socio-political development during the British colonial period. Evolutionary analysis indicates that Myanmar's socio-political transformation was not merely the result of a change in power, but a complex process of change involving the interplay of local traditions, colonial modernity, and global dynamics. The legacy of social and political structures formed during the colonial era profoundly influenced Myanmar's post-independence political development, including issues of national identity, inter-ethnic relations, and governmental stability. This study underscores that the British colonial era was a pivotal phase in shaping the socio-political configuration of modern Myanmar.